KODE ETIK NOTARIS DITINJAU DARI PERSPEKTIF ISLAM (KAJIAN ANALISIS SURAT AL BAQARAH AYAT 282) - BASRI EFFENDI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. H.M. Hasballah Thaib, MA, PhD2.  Prof. Dr. Muhd Yamin, SH, MS, CN3.  Notaris Dr. Syahril Sofyan, SH, MKn The content of Verse 282 of Surah Al-Baqarah with the profession of anotary is very closely related. There is the similarity between a Notary and thescribe in Verse 282 of Surah Al-Baqarah. The scribe in Verse 282 of Surah Al-Baqarah should comply with the procedures and ethics which are determined byAllah the Almighty: he has to be honest, impartial, and not to harm other people.The same is true to a Notary who has to comply with the law on NotarialProfession and Notarial Code of Ethics. The principles of Notarial Professionhave been regulated long time ago in Islam by the order to record buy and sellingtransaction, particularly debt and credit.Some prohibitions for a scribe in Verse 282 of Surah Al-Baqarah, amongothers, are: the prohibition to record a transaction unjustly and partially and torecord a transaction which is not in accordance with the principles of recording.It is suggested that he should not be reluctant to record as it is ordered by Allahthe Almighty, and that he should not reduce his debt. The witnesses should not bereluctant (to give information) when they are asked to witness. You should alwaysrecord the debt even though it is little or biguntil you can pay it off. The scribeand the witnessshould not hamper to each other, and you (witnesses) should notconceal witness.Keywords: Notary, Scribe, Code of Ethics, Verse 282 of Surah Al-Baqarah